An Indication of Gas Inflow in Clumpy Star-forming Galaxies near z ∼ 1: Lower Gas-phase Metallicities in Clumpy Galaxies Compared to Nonclumpy Galaxies - Visal Sok; Adam Muzzin; Pascale Jablonka; Vivian Yun Yan Tan; Z. Cemile Marsan; Danilo Marchesini; Gillian Wilson; Leo Y. Alcorn (The Astrophysical Journal)
Despite the ubiquity of clumpy star-forming galaxies at high-redshift, the origin of clumps are still largely unconstrained due to the limited observations that can validate the mechanisms for clump formation. We postulate that if clumps form due to the accretion of metal-poor gas that leads to violent disk instability, clumpy galaxies should have lower gas-phase metallicities compared to nonclumpy galaxies. In this work, we obtain the near-infrared spectrum for 42 clumpy and nonclumpy star-forming galaxies of similar masses, star formation rates, and colors at z  ≈ 0.7 using the Gemini Near-Infrared Spectrograph (GNIRS) and infer their gas-phase metallicity from the [N ii ] λ 6584 and H α line ratio. We find that clumpy galaxies have lower metallicities compared to nonclumpy galaxies, with an offset in the weighted average metallicity of 0.07 ± 0.02 dex. We also find an offset of 0.06 ± 0.02 dex between clumpy and nonclumpy galaxies in a comparable sample of 23 star-forming galaxies at z  ≈ 1.5 using existing data from the FMOS-COSMOS survey. Similarly, lower [N ii ] λ 6584/H α ratios are typically found in galaxies that have more of their UV _rest luminosity originating from clumps, suggesting that clumpier galaxies are more metal-poor. We also derive the intrinsic velocity dispersion and line-of-sight rotational velocity for galaxies from the GNIRS sample. The majority of galaxies have σ _0 / v _c  ≈ 0.2, with no significant difference between clumpy and nonclumpy galaxies. Our result indicates that clump formation may be related to the inflow of metal-poor gas; however, the process that forms them does not necessarily require significant, long-term kinematic instability in the disk.